(untitled) (TAMADDUN NURI JURNALI, 2024)
This article analyzes theoretical and methodological aspects of forming and improving linguo-cultural competence in English language lessons. The study explores the essence of this competence and its significance in enhancing students’ cultural knowledge based on linguistic, psychological, and psycholinguistic approaches. The author proposes modern methods and technologies aimed at developing linguo-cultural competence in learners.